Indonesian Political Policy in Overcoming Illegal Immigrant Problems in Indonesia - Angela Hutabarat (Institute of Computer Science (IOCS), 2020)
The purpose of this study is to find out why Indonesia has become a transit country or traffic line for illegal immigrants and to find out the extent of Indonesia's efforts in addressing this problem. This research is descriptive explanative in nature. The data were collected through literature review, known as Library Research. The technique used in analyzing the data is qualitative analysis. The result showed that the primary purpose of these illegal immigrants is that they seek a better life and security. They are seeking asylum in another country because there is no more dream or hope for a decent life. They mostly come from countries at war. They want to open a new chapter for their generations. They assume that Indonesia is the most appropriate place for them which is more like a dreamland for them. In addition, they have a strong network such as the trilogy links. This network has been around for ten years and has acted as board of protection and apply fundamental rules of all the countries concerned.